IMPLEMENTASI KEBIJAKAN BEASISWA PEMUDA TANGGUH DALAM MENDORONG PENINGKATAN KUALITAS PENDIDIKAN - Diva Ayu Pratiwi Firdaus; Agus Widiyarta (Halu Oleo University, 2024)
This research aims to determine how the Resilient Pemuda Tangguh Scholarship policy is implemented to encourage improvements in the quality of education, especially expanding access to education for Surabaya City residents from underprivileged family backgrounds. Qualitative methods with primary and secondary data were applied in this research. Primary data was obtained from interviews, observation and documentation. Meanwhile, secondary data was obtained from other research documents, documents from related agencies, and online news related to the Resilient Pemuda Tangguh Scholarship. After the data is collected, analysis is carried out through data reduction, data display, and inference/verification stages. The informants used by researchers include students from schools who have not submitted monthly reports for the last three months, and staff of the Sub-Coordinator of Public Welfare as the party responsible for the Resilient Pemuda Tangguh Scholarship policy. Based on the analysis of Smith's four theoretical variables, namely ideal policy, target group, implementing organization, and environmental factors, this policy is considered successful in improving the quality of education for underprivileged families, although there are still 1,800 participants who do not submit monthly reports due to lack of awareness of this obligation.